میر گل خان نصیرءِ شاعریءَ دروشمی تجربت: The Formatic Art in poetory of Mir Gul Khan Naseer - Mehr, Rahim Bakhsh; Hassain, Dr.Gul; Baloch, Hamid Ali; Gul, Nasreen (Hanken, 2014)
Mir Gul Khan Naseer is one the prominent Baloch writers who framed the modern Balochi Poetry. His poetic expression is innovative, devoted and artistic. His style of verse is unique concerning the other Baloch writers, in light of the fact that his elegant verses are modest and sensible. In this paper, all parts of artistic experiences in Mir’s verses will be focused.